THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE TEACHING - Turdimuradov Dilshod Choriyevich (European Science Publishing, 2026)
The integration of Artificial Intelligence (AI) into English Language Teaching (ELT) represents a transformative paradigm shift, offering personalized, adaptive, and efficient learning experiences while simultaneously presenting pedagogical, ethical, and technical challenges. This article synthesizes empirical evidence from recent meta-analyses, systematic reviews, and primary studies to explore AI's multifaceted role in enhancing linguistic skills such as speaking, writing, reading, and self-regulation, as well as affective factors including motivation, engagement, and anxiety reduction. Drawing on grounded theory and quantitative syntheses, it highlights AI's affordances in areas like speech recognition for pronunciation improvement and chatbots for conversational practice, alongside limitations such as technological biases and over-reliance risks. The discussion underscores the need for context-sensitive implementations, teacher training, and ethical frameworks to maximize AI's potential in diverse ELT contexts, particularly in non-English-dominant regions like Asia. Ultimately, AI is positioned not as a replacement for human educators but as a collaborative tool fostering inclusive, learner-centered education aligned with global sustainable development goals.
Keywords: Artificial Intelligence, English Language Teaching, Affordances, Challenges, Affective Factors, Personalized Learning, Speech Recognition, Chatbots, Meta-Analysis, Systematic Review.